The prevalence and risk factors of ventilator-associated pneumonia in intensive care units in Hospital Sultanah Bahiyah Kedah Malaysia - Yee, Loh Sze (2016)
Background: Ventilator associated pneumonia (VAP) is the commonest nosocomial infection in intensive care unit (ICU). We conducted a first study to collect local data on prevalence and risk factors of VAP in Hospital Sultanah Bahiyah (HSB), Kedah. Methodology: This prospective cohort surveillance was conducted on patients admitted to an adult medical-surgical ICU of a tertiary hospital from 1st August 2104 to 31st July 2105. VAP was diagnosed using Malaysia Registry of ICU (MRIC) criteria which included clinical manifestation, imaging and investigations. Results: In total, 297 patients were enrolled in this study. The prevalence of VAP was 22.0%. The most common causative pathogen was Acinetobacter sp. (31.8%). Multivariate analysis using simple logistic regression showed that risk factors for VAP were elderly patients (P=0.02; OR 1.02; 95% CI 1.00, 1.04), increase duration of ventilation (P<0.001; OR 1.49; 95% CI 1.35, 1.63), length of stay in ICU (P<0.001; OR 1.45; 95% CI 1.33, 1.59), length of stay in hospital (P<0.001; OR 1.07; 95% CI 1.04, 1.09), respiratory diseases (P=0.02; OR 2.25; 95% CI 1.17, 4.33), lung malignancy (P<0.001; OR 22.35; 95% CI 6.24, 80.09), previous antibiotic within three months (P=0.02; OR 2.25; 95% CI 1.17, 4.33), tracheostomy (P<0.001; OR 18.42; 95% CI 9.36, 36.23), reintubation (P<0.001; OR 25.69; 95% CI 12.73, 51.82), transportation for remote procedure (P<0.001; OR 20.76; 95% CI 9.65, 44.76), central venous line (CVL) insertion (P=0.04; OR 2.22; 95% CI 1.04, 4.76), continuous sedation (P=0.03; OR 1.85; 95% CI 1.04, 3.26) and without venous thromboprophylaxis (P=0.03; OR 2.05; 95% CI 1.09, 3.87). Conclusion: The prevalence and risk factors in our study were comparable to national and international data. We identify one new risk factor which is CVL insertion